The Effectiveness of e-Assessment in Improving the Quality of Learning and the Quality of Assessment on Financial Accounting Learning: A Literature Review - Susanti, Dessi; V., Yuhendri L. (JETL (Journal of Education, Teaching and Learning), 2024)
Financial accounting learning in higher education often faces challenges in ensuring that the evaluation methods used can effectively and efficiently measure students' understanding and skills. The background of this problem highlights the importance of improving the quality of assessment as an integral part of efforts to improve the quality of learning. This study aims to explore the role of e-Assessment, which is a digital technology-based assessment, in improving the quality of learning and the quality of assessment in financial accounting learning. The literature review method is used to identify, review, and synthesize various empirical studies, meta-analyses, and policy reports that discuss the implementation of e-Assessment in various educational contexts, including in the field of accounting. The results of this literature review show that the implementation of e-Assessment has several significant advantages. First, e-Assessment allows for more accurate and consistent measurement of student learning achievement, as it is able to reduce the subjectivity of assessment and increase transparency. Second, e-Assessment also improves administrative efficiency, by automating the process of assessing and reporting results, which in turn saves time and resources. In addition, e-Assessment encourages student involvement more actively in the learning process, as they get real-time feedback that helps them understand the strengths and weaknesses in their learning. In conclusion, e-Assessment not only supports more transparent and interactive learning, but also strengthens the validity and reliability of assessment results in financial accounting learning. Thus, e-Assessment can be an effective tool to support the improvement of the quality of learning and assessment in higher education, especially in the field of financial accounting